2001
DOI: 10.1902/jop.2001.72.11.1560
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Implantation in Fresh Extraction Sockets. A Controlled Clinical and Histological Study in Man

Abstract: The present study shows that when a screw-type dental implant is placed without the use of barrier membranes or other regenerative materials into a fresh extraction socket with a bone-to-implant gap of 2 mm or less, the clinical outcome and degree of osteointegration does not differ from implants placed in healed, mature bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
288
1
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(325 citation statements)
references
References 25 publications
23
288
1
13
Order By: Relevance
“…These results are consistent with several studies [22][23][24][25][26][27][28][29]. Schropp et al [22] reported that new bone formation occurs in infrabony defects associated with immediately placed implants in extraction sockets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with several studies [22][23][24][25][26][27][28][29]. Schropp et al [22] reported that new bone formation occurs in infrabony defects associated with immediately placed implants in extraction sockets.…”
Section: Discussionsupporting
confidence: 92%
“…Covani et al [24] observed that complete defect fill occurred in the peri-implant gaps following immediate and immediate-delayed implant placement. These observations are corroborated by human histologic studies that have shown spontaneous bone regeneration and osseointegration when peri-implant defects were less than 2 mm in a horizontal dimension [25]. Results of Spinato et al [26] suggested that immediate placed and immediate restored single implants are valuable therapeutic options in the maxillary arch and bone graft placement in horizontal gaps have no additional benefit in promoting better clinical outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…Only one implant was lost during that healing period. Thirty years after, Paolantonio et al (2001) compared histological sections of immediate implants and delayed implants and observed that they had a similar degree of osseointegration. Further histological observations on animal models have confirmed new bone formation from a quantitative and qualitative point of view ).…”
Section: Immediate Implant Placementmentioning
confidence: 99%
“…A number of materials have been tried as regenerative materials, including expanded polytetrafluoroethylene membranes, bioabsorbable membranes, demineralized freeze-dried bone allografts (DFDBA), freeze dried bone allografts, bone autografts, hard tissue replacement polymer, hydroxyapatite, xenografts, growth and differentiation factors, and particulate and block grafting materials. None of these materials has shown any superior clinical outcome in bone regeneration when compared in vivo, however 9,42) . Moreover, although DFDBA and modified hydroxyapatite granules have been used extensively in regenerative procedures, to the best of our knowledge, no studies to date have supported their use in immediate implant placement.…”
Section: Introductionmentioning
confidence: 99%